2003
DOI: 10.1364/ao.42.002897
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast-laser-radiation transfer in heterogeneous tissues with the discrete-ordinates method

Abstract: Here light propagation and radiation transfer of ultrafast laser pulses in heterogeneous biological tissues are simulated by use of the discrete-ordinates method (DOM). Formulations for solving the time-dependent radiation-transfer equation are deduced for three-dimensional geometries incorporating the Fresnel specularly reflecting boundary condition and characteristics of ultrafast laser pulses. The present method can treat both the incident laser intensity and the scattered radiation intensity from the walls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Other studies have shown that the diffusion approximation fails to predict the transmittance at early times for all optical thicknesses and also at long times for optically thin slabs [6]. In addition, Guo et al [7] showed that the diffusion approximation fails for both collimated radiation and strong anisotropically scattering media.…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…Other studies have shown that the diffusion approximation fails to predict the transmittance at early times for all optical thicknesses and also at long times for optically thin slabs [6]. In addition, Guo et al [7] showed that the diffusion approximation fails for both collimated radiation and strong anisotropically scattering media.…”
Section: Current State Of Knowledgementioning
confidence: 99%
“…In the case of optically thick slabs, the diffusion approximation fails for short times. This issue has also been discussed by Guo and Kim [20] in the transport of ultra-fast laser pulses in biological tissues. In addition, it is difficult to describe collimated sources using the diffusion approximation without carefully choosing the source terms [21].…”
Section: Current State Of Knowledgementioning
confidence: 87%
“…To limit thermal damage, external irradiation should be performed with a continuous-wave laser with cooling intervals (i.e., intermittent irradiation) [86] or with ultrafast irradiation with a pulsed laser (e.g., picosecond laser pulses) [109]. The combination of irradiation-and cooling intervals facilitates heat distribution to the solder-tissue interface and prevents excessive heat buildup in the underlying tissue.…”
Section: Status Quo Of Sslavw and Possible Solutions 341 Improvemementioning
confidence: 99%
“…In contrast to continuous-wave lasers that distribute heat to the deeper layer via conduction, the pulsed laser enables sufficient heat generation at the solder-tissue interface without over-coagulating the solder superficial layer. The pulsed laser produced stable welds with minimal thermal damage [109].…”
Section: Status Quo Of Sslavw and Possible Solutions 341 Improvemementioning
confidence: 99%